On Hegemonic Narratives, and the Facts regarding China's Response to COVID-19 Pandemic. Issue 4 (1st October 2020) - Saratchand, C.; Kaur, Navpreet
ABSTRACT: The COVID-19 pandemic has unleashed a multi-dimensional crisis that encompasses both the realm of public health and political economy. The divergences in the public health and economic policy responses among countries have resulted in an unleashing of a propaganda war. This paper is concerned with hegemonic narratives advocated by the mainstream media about China's response to the COVID-19 pandemic and the facts thereof. After examining in broad outline the temporal trajectory of the public health response in China and its underlying factors, the paper goes on to critically examine some contentious issues concerning the public health response to the COVID-19 pandemic in China that have been highlighted in the hegemonic narrative in the propaganda war over the COVID-19 pandemic. It is submitted that the divergence in the public health response of different countries is intimately related to the varied state of the neoliberal project therein. The paper concludes with a brief engagement with the political economy of the hegemonic narrative in the propaganda war.